Biocultural heritage – linking biological and cultural diversity: Cultural policies and practices (Research Announcements "Heritage BG", 2025)
Based on international policies and foreign investigations, attention is directed towards a problem poorly developed in our country – the essence and manifestations of biocultural heritage. A special emphasis is the interpretation of the rural scenery as a biocultural and multifunctional landscape. The author points out that in Bulgaria the relations between natural and cultural heritage are not yet an object of an integrated approach and adequate management of the processes for preserving biocultural resources for future objectives. As a good practice, a case of constructing a heritage based on biocultural achievements in the village of Kurtovo Konare, Plovdiv District, is analyzed. Heritage valorization is examined as a process of mobilizing resources (available and potential) and transforming capitals (after Pierre Bourdieu). The author indicates that the created symbolic capital has significant importance for local development and for the quality of life. References:Petrov, Petrova 2018: Petrov, Petur and Ivanka Petrova (eds.). Agrokulturni transformatsii v usloviyata na evropeizatsiya i globalizatsiya. Sofiya: IK ‘Gutenberg’Petrov, Ganeva-Raycheva 2021: Petrov, Petur and Valentina Ganeva-Raycheva (eds.). Rasteniya i hora. Priblizheniya kam biokulturnite vrazki. Sofiya: Erove, https://iefem.bas.bg/rastenia-i-hora.html.Agnoletti 2014: Agnoletti, Mauro. Rural Landscape, Nature Conservation and Culture: Some Notes on Research Trends and Management Approaches from a (Southern) European Perspective. – Landscape and Urban Planning, 126, 66-73.Agnoletti, Emanueli 2016: Agnoletti, Mauro and Francesca Emanueli (eds.). Biocultural Diversity in Europe. Florence: Springer.Agnoletti, Rotherham 2015: Agnoletti, Mauro and Ian Rotherham. Landscape and Biocultural Diversity. – Biodiversity and Conservation, 24 (13), 3155-3165, https://doi.org/10.1007/s10531-015-1003-8 .Barthel et al. 2013: Barthel, Stephan, Carole Crumley and Uno Svedin. Biocultural Refugia. Combating the Erosion of Diversity in Landscapes of Food Production. – Ecology and Society, 18 (4): 71 (www.ecologyandsociety.org/vol18/iss4/art71).Barthel et al. 2013a: Barthel, Stephan, Carole Crumley and Uno Svedin. Bio-Cultural Refugia. Safeguarding Diversity of Practices for Food Security and Biodiversity. – Global Environmental Change, 23, 1142-1152.Bourdieu 1994: Bourdieu, Pierre. Reasone pratiques. Sur la theorie de l’aicion. Paris: Édition du Seuil.Bourdieu, Vacquant 1992: Bourdieu, Pierre and Loïc J. D. Vacquant. Réponses. Pour une anthropollogie reflexive. Paris: Édition du Seuil.Bridgewater, Rotherham 2019: Bridgewater, Peter and Ian Rotherham. A Critical Perspective on the Concept of Biocultural Diversity and its Emerging Role in Nature and Heritage Conservation. – People and Nature, vol. 1, Issue 3, 291-304, https://besjournals.onlinelibrary.wiley.com/doi/full/10.1002/pan3.10040.Crumley et al. 2018: Crumley, Carole L., Tommy Lennartsson and Anna Westin (eds.). Issues and Concepts in Historical Ecology: The Past and Future of Landscapes and Regions. Cambridge: Cambridge University Press.Eriksson 2018: Eriksson, Оve. What is Biological Cultural Heritage and why should We Care about it? An Example from Swedish Rural Landscapes and Forests. – Nature Conservation, 28, 1-32, https://natureconservation.pensoft.net/article/25067/.Lindholm, Ekblom 2019: Lindholm, Karl-Johan and Anneli Ekblom. Framework for Exploring and Managing Biocultural Heritage. – Anthropocene, 25, 2-9.Maffi 2001: Maffi, Luisa. Introduction. In: Maffi, Luisa (ed.). On Biocultural Diversity. Linking Language, Knowledge, and the Environment. Washington: Smithsonian, 2001, 1–50.Maffi 2005: Maffi, Luisa. Linguistic, Cultural, and Biological Diversity. – Annual Review of Anthropology, 34 (1), 599–617.Maffi, Woodley 2010: Maffi, Luisa and Ellen Woodley. Biocultural Diversity Conservation. A Global Sourcebook. London, Washington: Earthscan.Pieroni, Quave 2014: Pieroni, Andrea and Cassandra L. Quave (eds.). Ethnobotany and Biocultural Diversities in the Balkans: Perspectives on Sustainable Rural Development and Reconciliation. New York: Springer.Rotherham 2015: Rotherham, Ian. Bio-cultural Heritage and Biodiversity: Emerging Paradigms in Conservation and Planning. – Biodiversity and Conservation, 24 (13), 3405-3429.Rozzi 2018: Rozzi, Ricardo. Biocultural Homogenization: A Wicked Problem in the Anthropocene. In: Rozzi et al. (eds.). From Biocultural Homogenization to Biocultural Conservation, 21-48.Международни документи:Конвенция 2003: Конвенция за опазване на нематериалното културно наследство, https://ich.unesco.org/doc/src/00009-BG-PDF.pdfUNESCO 2008: Operational Guidelines for the Implementation of the World Heritage Convention. UNESCO World Heritage Centre, Paris, https://whc.unesco.org/en/guidelines/UNESCO SCBD 2010: UNESCO – CBD Joint Program Between Biological and Cultural Diversity. UNESCO, Paris, http://www.unesco.org/new/en/naturalsciences/special-themes/biodiversity-initiative/biodiversity-culture/unesco-cbd-joint-programme/UNESCO SCBD 2014: Florence Declaration on the Links Between Biological and Cultural Diversity. UNESCO, Florence, http://www.landscapeunifi.it/images/pdf/UNESCO-CBD_JP_Florence_Declaration.pdfCBD 2018: Voluntary Glossary of Key Terms and Concepts within the Context of Article 8(j) and Related Provisions. – Conference of the Parties to the Convention on Biological Diversity. Fourteenth meeting Sharm El-Sheikh, Egypt, 17-29 November 2018, https://www.cbd.int/doc/decisions/cop-14/cop-14-dec-13-en.pdf. 3-en.pdf
Keywords: local genetic resources; knowledge and skills; integral approach; transformation of capitals; valorization